A socio-environmental analysis of land alienation and resettlement in Ga-Rankuwa, c. 1961 to 1977 - Kgari-Masondo, Maserole Christina (Faculty of Humanities, University of the Free State, 2013)
This article presents a historical case-study in forced removals and its ramifications from 1961 to 1977 from the perspective of socio-environmental history. The focus area is Pretoria (South Africa) in a resettlement area called Ga-Rankuwa whose community was displaced from Lady Selborne in the 1960s. The article demonstrates that forced removals did not only result in people losing their historical land and material possessions but also their sense of being and connectedness. The focus is on the changing perceptions of people in the midst of their land loss, an area of study that is generally underexamined in academia. In Lady Selborne, blacks were displaced from an area that was agriculturally fertile, close to the city centre of Pretoria and relocated to infertile Ga-Rankuwa on the outskirts of the city. This resettlement resulted in many of those relocated being prevented from engaging in food production, which was in turn an affront to Sotho-Tswana culture and religion with its emphasis on land as lefa: a bequest that has to feed its inhabitants. This mind-set resulted in forced removals and in turn led blacks to disregard environmental issues. Ga-Rankuwa became degraded with litter, soil erosion and dongas, especially in the 1970s, as people realised that there was no hope of returning to Lady Selborne.
Keywords: Ga-Rankuwa; Socio-environmental history; Land alienation; Forced removals; Resettlement; Lady Selborne; Environment; Degradation